(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effects of prenatal exposure to sodium phenytoin on survival and hatching of chick embryos. Study Design: Experimental study. Place and Duration of Study: This study was carried out in the Anatomy Department, Regional Centre of College of Physicians and Surgeons, Islamabad from January 2012 to January 2013. Materials and Methods: The study was carried out on three experimental (B1,B2,B3) and three control (A1,A2,A3) groups. The chick embryos of the experimental groups were injected with 3.5 mg of sodium phenytoin per egg whereas the controls were administered same volume of normal saline just before incubation. The experimental group was dissected on day 4, day 9 and day 22 or hatching whichever was earlier. Theompared with age-matched controls. Results: Survival was less in the experimental groups as compared to the controls. The percentage of mortality was 3.84% in group B1, 14.28% in group B2 and 21.42% in group B3. This difference between control and experimental groups was found to be statistically significant (p<0.05). In group B3, 90% of the live chicks were able to crack open the shell on their own. Rest of the chicks had to be assisted after waiting till 22nd day of the incubation. All of the chicks belonging to the control group A3 cracked open the shell on their own on the 21st day of incubation but this difference between groups A3 and B3 regarding mode of hatching was found to be statistically insignificant (p 0.1812). Conclusion: In this study, prenatal sodium phenytoin exposure resulted in decreased chick embryo survival with increasing embryonic age and increased duration of exposure but there was no significant effect on the hatching of the chicks.